2014
DOI: 10.1002/bdm.1820
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a New Measure of Intuition: The Types of Intuition Scale

Abstract: The Types of Intuition Scale (TIntS) measures three types of intuition identified in a literature review by Pretz and Totz (2007): holistic, inferential, and affective. Holistic intuitions integrate diverse sources of information in a Gestalt‐like, non‐analytical manner; inferential intuitions are based on previously analytical processes that have become automatic; and affective intuitions are based on feelings. Current intuition measures inadequately assess these distinct types. We report four validity studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 52 publications
(71 reference statements)
3
91
0
Order By: Relevance
“…In developing a comprehensive framework for both the conceptualisation and measurement of intuition, Pretz et al (2014) argued that affective, inferential, and holistic intuition represented distinct types of information processing within a unifying intuitive mode. A concise definition of these three types are presented below:…”
Section: Intuition Based Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…In developing a comprehensive framework for both the conceptualisation and measurement of intuition, Pretz et al (2014) argued that affective, inferential, and holistic intuition represented distinct types of information processing within a unifying intuitive mode. A concise definition of these three types are presented below:…”
Section: Intuition Based Decision-makingmentioning
confidence: 99%
“…We then turn to the issue of deep-level diversity and the need to develop more nuanced and empirically grounded explanatory frameworks which consider the two-way effects of cognitive diversity in decision-making teams in general, and of intuitive decision styles in particular (Klein, Knight, Ziegert, Lim, & Saltz, 2011;Pretz et al, 2014). Such frameworks are of particular relevance to the entrepreneurship literature given the uncertain, high-risk, time pressured, and emotionally challenging nature of the entrepreneurial process and the subsequent reliance on intuition in that domain (Baron, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We question their claim that the Bimplicit system cannot, by itself, be creative above and beyond the creativity exhibited by evolutionary algorithms in nature -in a blind manner.^This may be consistent with how the implicit system is characterized in some dual processing theories (e.g., Evans, 2003) but not in others, and particularly those in the creativity literature. Judgments driven by the implicit system can arise due to different types of intuitions, some of which reflect statistical and inferential regularities that are far from blind (Pretz et al, 2014;see Sowden, Pringle, & Gabora, 2015, for a discussion of the relationship between dual processing models and creativity). Here the implicit system is generally characterized as giving rise specifically to ideas that have particular features which, though seemingly Bremote^in the given context, are relevant to it (e.g., Finke, Ward, & Smith, 1992).…”
Section: Implications Of Evolutionary Theory For Dual Processing Modelsmentioning
confidence: 99%
“…Some concluded that intuitive nurses make a holistic judgment in clinical settings, and integrate diverse information to make a decision. 16 Miller argued these nurses were willing to act on their intuitions, were skilled clinicians, incorporating a spiritual component into their practices, expressed an interest in the abstract nature of things, and were risk takers. 2 It is also believed that critical care nurses use intuition as best practice in complicated and emergency clinical situations, 17 because they care for more critically ill patients.…”
Section: Introductionmentioning
confidence: 99%